Place in Service-Learning: A Case Study of the Connection Between Sense of Community and Service-Learning with Rural Teachers - Beyer Hansen, Faith; Gregory, Anne (International Journal of Research on Service-Learning in Teacher Education, 2015)
Research on teacher motivation to implement service-learning is yet to explore the role of teachers sense of community as a defining factor in implementing service-learning. This case-study of six teachers explores the intersection of rural teachers motivation to implement service-learning and their sense of community. The Sense of Community Index (SCI-2), as well as qualitative data from interview and observation, was analyzed to understand what, if any, connection exists between a teachers high sense of community and his or her use of service-learning. Exploratory findings indicate that rural teachers with a high sense of community are more likely to implement service-learning than their low sense of community colleagues. These findings suggest that the SCI-2 may be a useful tool in working with pre-service and practicing teachers to predict and support the development of teachers sense of community and their commitment to service-learning.